2016
DOI: 10.3390/nu8040242
|View full text |Cite
|
Sign up to set email alerts
|

Cocoa Diet Prevents Antibody Synthesis and Modifies Lymph Node Composition and Functionality in a Rat Oral Sensitization Model

Abstract: Cocoa powder, a rich source of polyphenols, has shown immunomodulatory properties in both the intestinal and systemic immune compartments of rats. The aim of the current study was to establish the effect of a cocoa diet in a rat oral sensitization model and also to gain insight into the mesenteric lymph nodes (MLN) activities induced by this diet. To achieve this, three-week-old Lewis rats were fed either a standard diet or a diet with 10% cocoa and were orally sensitized with ovalbumin (OVA) and with cholera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
62
4
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 24 publications
(80 citation statements)
references
References 66 publications
13
62
4
1
Order By: Relevance
“…In order to find out what happened in Th1/Th2-associated antibody isotypes, the concentration of specific IgG1, IgG2a, IgG2b, IgG2c, and IgE antibodies was determined. The oral sensitization caused the synthesis of antibodies belonging to IgG1, IgG2a, and IgG2b isotypes, as previously reported [20,22]. The 0.5% hesperidin-enriched diet did not significantly modify the levels of these anti-OVA antibodies (Table 4).…”
Section: Resultssupporting
confidence: 83%
“…In order to find out what happened in Th1/Th2-associated antibody isotypes, the concentration of specific IgG1, IgG2a, IgG2b, IgG2c, and IgE antibodies was determined. The oral sensitization caused the synthesis of antibodies belonging to IgG1, IgG2a, and IgG2b isotypes, as previously reported [20,22]. The 0.5% hesperidin-enriched diet did not significantly modify the levels of these anti-OVA antibodies (Table 4).…”
Section: Resultssupporting
confidence: 83%
“…However, a recent study on the gene expression of mesenteric lymph node cells shows that certain molecules present on antigen-presenting cells (dendritic cells) were modified by this diet. In particular, a cocoa diet increased the gene expression of CD11c and OX40L (31) (Figure 1A). It has been suggested that, in a model of oral sensitization, a subset of dendritic cells (CD11c + , CD103 + , and CD8 + ) that migrates and activates in the mesenteric lymph nodes seems responsible for the Th2 polarization in this model (46).…”
Section: Cocoa Influences Composition and Functionality Of Primary Anmentioning
confidence: 99%
“…The increase of Tc cells in mesenteric lymph nodes was accompanied by a higher proportion of activated cells (CD25 + CD8 + cells) and cells expressing the αE-integrin (CD103 + CD8 + cells) and a lower proportion of cells bearing L-selectin (CD62L + CD8 + cells) (31) (Table 2). CD103 is a subunit of the αE-integrin that can mediate cell adhesion and migration to the gut (35), whereas L-selectin is involved in lymphocyte rolling on the endothelium and the homing to secondary lymphoid tissues (36).…”
Section: Cocoa Influences Composition and Functionality Of Primary Anmentioning
confidence: 99%
“…This issue provides an opportunity to update current knowledge about some examples of the six subclasses of the flavonoid compounds and their effects—even at molecular level—on immunity and inflammation, but also in inflammatory-mediated diseases such as insulin-resistance obesity, cardiovascular disease and even in cancer. The Special Issue contains six review papers [13,14,15,16,17,18] and eight research papers [19,20,21,22,23,24,25,26] on the current knowledge in the field. Contributions are from countries in Africa (South Africa), America (Brazil), Asia (China, Korea, Japan and Taiwan) and Europe (Germany, Spain and Switzerland).…”
mentioning
confidence: 99%
“…The conclusion of this first clinical study to evaluate the effect of those flavonoids on the inflammatory profile of such patients undergoing antiretroviral therapy, indicates that 65 g dark chocolate is able to increase high-density lipoprotein cholesterol (HDL-c) concentrations [21]. A different effect of cocoa is shown by Camps-Bossacoma et al [22], who reported the tolerogenic effects of cocoa on a rat model of oral sensitization. This study, focused on acquired immunity, reveals the changes produced by cocoa intake on mesenteric lymph nodes, which eventually prevent oral immunization to a food allergen.…”
mentioning
confidence: 99%